HOLE DETECTION AND HEALING IN HYBRID WIRELESS SENSOR NETWORK - Kalwaghe, Samidha N; Dusane, Atul Vasudev (APTIKOM Publisher, 2016)
The emerging technology of wireless sensor network (WSN) is expected to provide a broad range of applications, such as battlefield surveillance, environmental monitoring, smart spaces and so on. The coverage problem is a fundamental issue in WSN, which may cause due to low residual energy of nodes or poor installment. But in order to get full coverage of sensing area Coverage problem must be avoided. If the problem is unavoidable the coverage hole must be healed. Current hole healing algorithms uses complicated hole detection strategies like TENT rule. This project seeks to address the problem of hole detection and healing in mobile WSNs by deploying mobile sensors in the network, which is called hybrid sensor network. An enhanced hole detection and healing method (MHEAL) is proposed. MHEAL is a distributed and localized algorithm that operates in two distinct phases. First, is Distributed Hole Detection (DHD) proposed to identify the boundary nodes and discover holes. Second, is hole healing which uses a virtual forces based hole healing approach where only the nodes located at an appropriate distance from the hole and the nodes having maximum energy will be involved in the healing process. Unlike existing algorithms, proposed algorithm uses QURD based node detection and energy efficient Hole healing and thus solves the problem of hole with 100% coverage, minimum node movements and minimum node distance travelled thus giving a cost efficient solution.